2020
DOI: 10.1016/j.heliyon.2020.e05321
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical traits in coriander affected by plant growth-promoting rhizobacteria under salt stress

Abstract: Salinity is a major environmental stress that limits crop production worldwide. It is well-understood that environmental adaptations, physiological and biochemical traits adjust salinity tolerance in plants, but imparting the knowledge gained towards crop improvement remain arduous. Utilizing the potentially of beneficial microorganisms present in the rhizosphere is an alternative strategy to improve crop production under optimal or stress conditions. The current study aims at examining the ability of plant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Plant growth promoting rhizobacteria (PGPR), has also been shown to increase tolerance of plants to drought stress ( Pereira et al., 2020 ). Rabiei et al. (2020) reported similar mechanism, using PGPR, to increase plant tolerance to salinity in ( Coriandrum sativum L ).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Plant growth promoting rhizobacteria (PGPR), has also been shown to increase tolerance of plants to drought stress ( Pereira et al., 2020 ). Rabiei et al. (2020) reported similar mechanism, using PGPR, to increase plant tolerance to salinity in ( Coriandrum sativum L ).…”
Section: Introductionmentioning
confidence: 79%
“…Plant growth promoting rhizobacteria (PGPR), has also been shown to increase tolerance of plants to drought stress (Pereira et al, 2020). Rabiei et al (2020) reported similar mechanism, using PGPR, to increase plant tolerance to salinity in (Coriandrum sativum L). Plant also use physiological characteristics to adapt to water stress environments through maintaining high water status regardless of soil moisture content (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Studies have shown that biofertilizer such as PGPRs together with salinity stress affect the growth, yield and physiology of coriander plants [ 14 ]. In our experiments, lower doses of adapted inoculum (T3) showed better plant properties and similar results to chemical fertilization (T2).…”
Section: Discussionmentioning
confidence: 99%
“…This trait is desirable for human coriander consumption but it can also be associated with soil plant stress due to salinity conditions. On the other hand, the height of plants is not directly correlated with type of fertilization [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation